PERCEIVED ACCEPTABILITY OF ASSISTED REPRODUCTIVE TECHNOLOGY (ART) AS TREATMENT MODALITY FOR INFERTILITY IN IJEBU LAND, OGUN STATE, NIGERIA (2014)
Infertility is a social and cultural problem that makes People Living with Infertility (PLWI) to seek solutions through different means. The 2007 - 2010 clinic records at General Hospital, Ijebu-Ode, a secondary health care facility that serves several communities in Ijebuland, have shown that the prevalence of infertility is on the increase. Assisted Reproductive Technology (ART) is a major breakthrough or innovation for the treatment of infertility. In Nigeria, previous studies have focused on the importance of ART with little attention paid to the sociocultural factors which affect its acceptance. This study, therefore, examined the sociocultural factors that have potential to influence the perception and acceptance of ART in Ijebu, Ogun State, Nigeria. Innovation Adoption Theory by Rogers (1995) and Health Belief Model by Rosentock (1978) were employed as guide with cross-sectional survey design adopted using a three-stage sampling technique. Two local government areas (LGAs) - Ijebu-Ode and Ijebu North - were purposively selected followed by a random selection of five enumeration areas in each LGA. Ten Key Informant Interviews (KIIs) were conducted with ART specialists, traditional birth attendants, religious and opinion leaders to elicit information on their awareness and perception of ART. Also, 10 in-depth interviews were conducted with female and male clients, using ART on the challenges associated with the acceptance of ART. A structured questionnaire was administered to 732 household heads in the LGAs to elicit information on demographic and sociocultural factors, perception, awareness, knowledge and decision making about ART. Quantitative data were analysed using descriptive statistics and Chi-square at 0.05 level of significance while qualitative data were analysed thematically. Respondents’ age was 35.8±7.5 years, 60.7% were male, 59.6% had tertiary education and 63.3% were Christians. About 17.8% were aware and 17.3% had knowledge about ART. Majority (82.7%) of the respondents was not favourably disposed to the use of ART and few (21.3%) had negative perception of it. There was a significant relationship between level of education and perceived acceptability of ART (χ2 =7.793, df=9). Respondents with tertiary education (11%) compared to 5.7% with lower levels of education were favourably disposed to the use of ART. There were no significant relationships between age, income, duration of marriage, accessibility and perceived acceptability of ART. There were significant relationships between perceived ART acceptability and gender ((χ2=13.24, df=2), marital status (χ2=24.612), religion (χ2=15.769, df=6) and family support (χ2=2.987, df=3). Most PLWI did not use ART facilities on religious ground, stigmatisation, and poor level of awareness, knowledge and inaccessibility. Financial and social costs were perceived as hindrances to acceptability of ART. Husbands of women living with infertility were not in support of ART because of stigmatisation and doubts by the family about the identity of the child. Most clients on ART had tertiary education and accepted it as the last option and usage was based on joint decision of husbands and their wives Assisted Reproductive Technology is not a common practice in the study area due to sociocultural factors. Public enlightenment and social-marketing are needed to promote the adoption of the technology by persons with infertility.